Semantics and specificities of functioning of nouns with augmentative suffixes in informal internet-communication (based on the materials of Russian-speaking blogs) - Evgeniya V. Skachkova (Вестник Самарского университета: История, педагогика, филология, 2022)
This article is devoted to the study of non-substantive augmentatives as part of the semantic-derivative category of the intensity of a non-procedural feature in modern Russian. The study is based on data extracted from the General Internet Corpus of the Russian Language (hereinafter referred to as GIKRYA), namely, from its LiveJournal subcorpus. The analyzed material is distinguished by expressiveness, emotionality and evaluativeness, which is reflected in its high linguo-creativity and allows studying not only ordinary, but also potential derivatives. The article analyzes the functional and semantic features of suffixes-augmentators of nouns, highlights the typical meanings of the most productive formants – -ищ-, -ин(а), -уг(а) (орф. -юг(а)), -юк(а). Substantive augmentatives are often used in statements with multiple intensification, interacting in context with lexical markers of feature intensification. The frequency of such use of the studied derivatives allows us to conclude that augmentative suffixes have a weak potential for intensification, and, therefore, should be attributed to the periphery of the semantic-word-building category of intensity.